Metagenomic Analysis of Antibiotic Resistance Genes in Untreated Wastewater From Three Different Hospitals - Guo, Xiurong; Tang, Nan; Lei, Hui; Fang, Qi; Liu, Li; Zhou, Quan; Song, Can (Frontiers in Microbiology, 2021)
Hospital wastewater is the main source of antibiotic-resistant bacteria and antibiotic resistance genes (ARGs) compared with other pollution sources in the environment. Expanding our knowledge on the bacterial composition of hospital wastewater will help us to control infections in hospitals and decrease pathogen release into the environment. In this study, a high-throughput sequencing-based metagenomic approach was applied to investigate the community composition of bacteria and ARGs in untreated wastewater from three different types of hospitals. In total, 130 phyla and 2,554 genera were identified from the microbiota of the wastewaters, and the community composition of bacteria from the three hospitals was significantly different at both the phylum and genus levels. Total antibiotic resistance gene analysis using the Antibiotic Resistance Genes Database and Comprehensive Antibiotic Resistance Database revealed that the microbiota in the wastewaters from the three hospitals harbored different types and percentage of ARGs, and the composition of the ARGs was specific to the hospital type. In summary, our findings demonstrated a widespread occurrence of ARGs and ARG-harboring microbiota in untreated wastewaters of different hospitals, suggesting that relative protection should be measured to avoid infection. Concurrently, hospital wastewater should be treated more specifically for pathogens that are present in it before discharge into the urban sewage system.